Prison Inspection and Monitoring: The Need to Reform European Law and Policy - Rogan, Mary (My University, 2019)
Prison inspection and monitoring bodies are important safeguards against breaches of human rights. In recent years, prison inspection and monitoring has become a key focus for international human rights standards, particularly through the introduction of the Optional Protocol to the Convention against Torture (OPCAT) and the UN’s Standard Minimum Rules for the Treatment of Prisoners, which recognize the need for robust and effective systems of prison oversight. This article contends that European legal standards on inspection and monitoring have not kept pace with international developments. The content of European law concerning domestic-level prison inspection and monitoring is not clear, nor has it been consolidated or examined in depth. Through engaging in comparative analysis with international instruments, this article analyses standards promulgated by Council of Europe and European Union bodies on inspection and monitoring, arguing that they need reform in light of international developments. Taking the opportunity presented by the revision process for the European Prison Rules and associated commentary, the article proposes improvements to European legal frameworks. It welcomes proposals for stronger powers for inspection and monitoring bodies, advocates for a specific instrument on prison inspection and monitoring and calls for more empirical understanding of how such bodies operate in practice.
PUBLISHED
https://link.springer.com/article/10.1007/s10610-019-09420-8
Keywords: Prisons; European penal policy; European human rights; Inspection and monitoring; European prison rules; International human rights law; OPCAT; Mandela rules